2015
DOI: 10.2308/ajpt-51292
|View full text |Cite
|
Sign up to set email alerts
|

Audit Firms' Client Acceptance Decisions: Does Partner-Level Industry Expertise Matter?

Abstract: SUMMARY This study examines whether auditor industry expertise affects firms' client acceptance decisions. Analyzing listed firms in Taiwan, where audit partners' signatures are disclosed on the audit report, we find that partner-level industry specialists, rather than firm-level industry specialists, are less likely to accept clients with higher audit risk. We also provide weak evidence that partner-level industry specialists are less likely to accept clients with higher financial risk. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
1
22
0
4
Order By: Relevance
“…In addition, whether the auditor has the industry expertise also affects the audit quality. Hsieh, Lin (2016) found that it is the auditor industry expertise rather than the firm industry expertise that filters the customers with high risk, indicating that the auditor industry expertise will affect the customer selection and audit quality. Wang, Song & Xu (2018) studied the relationship between auditor's personal characteristics and industry expertise, and found that auditor's industry expertise can effectively alleviate the asset mispricing of listed companies, and the impact is more significant when auditor's independence is strong.…”
Section: Literature Review On the Characteristics Of Firms And Auditorsmentioning
confidence: 99%
“…In addition, whether the auditor has the industry expertise also affects the audit quality. Hsieh, Lin (2016) found that it is the auditor industry expertise rather than the firm industry expertise that filters the customers with high risk, indicating that the auditor industry expertise will affect the customer selection and audit quality. Wang, Song & Xu (2018) studied the relationship between auditor's personal characteristics and industry expertise, and found that auditor's industry expertise can effectively alleviate the asset mispricing of listed companies, and the impact is more significant when auditor's independence is strong.…”
Section: Literature Review On the Characteristics Of Firms And Auditorsmentioning
confidence: 99%
“…Furthermore, we call for theoretical and empirical research on the supply side of auditor choice (e.g., auditors' client acceptance ;Hsieh & Lin, 2016;Huang, Raghunandan, & Rama, 2009;Johnstone, 2000;Khalil & Mazboudi, 2016;Kwon, 1996) and the construction of audit quality from the auditors' perspective (Christensen, Glover, Omer, & Shelley, 2016;Qi, Li, & Tian, 2015). Auditor choice is a two-party contractual arrangement affecting a range of factors.…”
Section: Francismentioning
confidence: 99%
“…Bên cạnh các quy định của chuẩn mực kiểm toán, khá nhiều nghiên cứu trước đã phát hiện các nhân tố ảnh hưởng đến quyết định chấp nhận hay duy trì khách hàng như: Rủi ro kiểm toán, rủi ro kinh doanh của khách hàng và rủi ro kinh doanh của công ty kiểm toán. Ba loại rủi ro này có ảnh hưởng ngược chiều đến quyết định chấp nhận hay duy trì khách hàng (Ebaid, 2011;Hsieh & Lin, 2016;Johnstone, 2000;Johnstone & Bedard, 2003;Johnstone & Bedard, 2004;Ouertani & Damak-Ayadi, 2012). Tại Việt Nam, cho đến nay, có rất ít nghiên cứu về các nhân tố ảnh hưởng đến quyết định chấp nhận hay duy trì khách hàng.…”
Section: Giới Thiệuunclassified